The Power of Framing: Examining BBC's Representation of the Ukraine War in March 2022 - Hermilania, Hermilania (Anaphora : Journal of Language, Literary, and Cultural Studies, 2024)
This research examines the framing analysis of news coverage in BBC Articles Site about the War in Ukraine during March 2022. The purpose of this research is to analyze the messages conveyed to readers and the elements that construct the news based on the framing analysis concept proposed by Zhongdang Pan and Gerald M. Kosicki. The method used is descriptive qualitative research with framing analysis technique, employing document study to collect news articles. The results reveal that BBC Media's framing of the Russia-Ukraine war in March 2022 predominantly emphasized the suffering and victimization of Ukrainian citizens and military. The syntactical structure analysis shows that BBC consistently used emotive headlines, sympathetic leads, and strategic quotations that favored the Ukrainian perspective, while depicting Russia as the aggressor. The script structure analysis demonstrates that BBC reports prioritized humanitarian aspects over military or political dimensions, highlighting civilian casualties and refugee crises. The thematic structure reveals a consistent narrative portraying Ukraine as a democratic nation defending itself against an authoritarian invader. The rhetorical structure analysis indicates extensive use of photographs depicting Ukrainian suffering, graphics illustrating Russian military advances, and emotional language that reinforced the victimization frame. The findings have important implications for media literacy education, highlighting how even respected news organizations employ specific framing devices that can shape public perception of international conflicts. Additionally, the research contributes to understanding how traditional journalistic values of objectivity are challenged when covering asymmetrical conflicts with clear geopolitical stakes for Western democracies.